(untitled) (Research, Society and Development, 2021)
Dermatophytes are keratinophilic fungi and the causative agent of dermatophytosis in animals and people. In the pathogenesis of this disease, enzymes such as DNase, gelatinase, lipase, keratinase, elastase, and collagenase are highlighted. This work aimed to verify the production of these enzymes by clinical and environmental isolates of dermatophytes. Environmental strains were obtained by the Vanbreuseghem technique (1952), using soil samples from different Brazilian locations. The clinical samples were obtained from animal hair and crust sent to the Veterinary Microbiological Diagnostic Service/UFRRJ. The enzymatic evaluation of the dermatophytes was made by spectrophotometer absorbance readings (collagenase, elastase, and keratinase), degradation halo formation in Petri dishes (DNase and lipase) and tube liquefaction (gelatinase). The clinical isolates were Microsporum canis (11), Nannizzia gypsea (7), N. nana (2), Trichophyton mentagrophytes (4) and Trichophyton sp. (6). The environmental isolates were N. gypsea (25), N. nana (1) and Trichophyton sp. (4). There was no statistically significant difference in keratinase, elastase, lipase and gelatinase production between the clinical and environmental isolates groups. There was a statistically significant difference in collagenase and DNase production. It is concluded that both clinical and soil samples are capable of producing enzymes related to dermatophyte infection.